IMPLEMENTASI KEBIJAKAN PEMBERIAN HAK GUNA USAHA - Halomoan Sirait, Janri Wolden (Jurnal Ilmu Administrasi Negara, 2017)
Abstract: Policy Implementation for Giving Cultivate Right. This study aims to determine Policy Implementation for Giving Cultivate Right the National Land Agency Regional Office of Riau Province. This research is a descriptive study with qualitative approach. Informants in this study are the people who play a role in the administration of leasehold in the Regional Office of Riau Province National Land Agency. Data collection technique were interview, observation and documentation. The results of this study showed that the implementation of the policy of granting rights to cultivate the Nasioanal Land Agency Regional Office of Riau province has not gone up, meaning that implementation is happening in the field is still not effective. Still the presence of companies that do not have the right to cultivate while they have been operating.